2001
DOI: 10.1117/12.411637
|View full text |Cite
|
Sign up to set email alerts
|

<title>New design schemes for x-ray waveguides based on multiple guiding layers and two-dimensional nanostructures</title>

Abstract: Planar x-ray waveguide structures can be used as resonant beam coupling devices to produce a coherent and divergent x-ray line source with cross-sections in the sub-micrometer range. This article reviews the basic x-ray optical properties of such devices and generalizes the principle of resonant x-ray beam coupling to waveguides containing multiple guiding layers. In such a device, several coherent beams of a width on the order of 100 A to 1000 A can be extracted at the end of the waveguide. Besides coherent d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 2 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…Complementing other cohérent focusing elements like Fresnel zone plates, Bragg Fresnel lenses, or bent crystal optics, we discuss récent advances in x-ray waveguide optics. leading to beam cross sections determined by the width W of the guiding layer, ranging from several 100 down to 10 nm [7]. Such beam with a cross section in the range between 10-100 nm could open up a whole new range of applications in scattering, microscopy and spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Complementing other cohérent focusing elements like Fresnel zone plates, Bragg Fresnel lenses, or bent crystal optics, we discuss récent advances in x-ray waveguide optics. leading to beam cross sections determined by the width W of the guiding layer, ranging from several 100 down to 10 nm [7]. Such beam with a cross section in the range between 10-100 nm could open up a whole new range of applications in scattering, microscopy and spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, X-ray diffraction with a spatial resolution of $100 nm in one dimension has been demonstrated (Di Fonzo et al, 2000). We have recently shown that even beam widths of less than 100 A Ê can be achieved by the use of X-ray waveguides in the socalled resonant beam coupling devices (Pfeiffer et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Tapered waveguides channels with an exit size down to 16.5 nm × 14.6 nm have been reported recently [23]. In [30,31], the single guiding film was generalized to an array of planar wavguides, and in [32,33], the cladding was generalized to a multilayer structure.…”
Section: Introductionmentioning
confidence: 99%
“…With thin film deposition techniques, notably 8 nm [27,28] for the given material could be reached in a planar thin film waveguide with an optimized cladding material (Mo/C /Mo structure embedded in Ge wafers [29]). Furthermore, the single guiding film [30,31] or the cladding film [32,33] can be generalized to a multilayer structure. Therefore, for purposes of the highest beam confinement or to exploit novel geometries as in this thesis, waveguiding in only one dimension as in an array of thin planar films, is suitable and attractive, owing to a better control of layer sequences.…”
Section: Introduction Scope and Outline Of The Thesismentioning
confidence: 99%